FEEDING PRACTICES AND ITS ASSOCIATION WITH NUTRITIONAL STATUS OF UNDER 5 CHILDREN - A CROSS-SECTIONAL STUDY IN NORTHERN PART OF INDIA (Proceedings of the International Conference on Public Health, 2023)
Undernutrition is still a serious health concern for children, particularly in South-East Asia. An estimated 45% of all child deaths, are attributed to undernutrition. Malnutrition during early childhood can have lifelong consequences, including impaired cognitive development, increased susceptibility to infections, and reduced productivity in adulthood. The development and growth of young children under the age of five are significantly influenced by optimal feeding practices. The objectives of the study were to assess the feeding practices and nutritional status of children under 5 years of age, and to find out the association of feeding practices with their nutritional status. This was a community based cross-sectional study with a sample size of 815. The children aged 0-59 months from rural and urban areas of Aligarh were assessed using structured questionnaire, and WHO anthropometric indices and Z-score were calculated using WHO Anthro software. The data was analyzed using SPSS IBM 20.0. It was found that 45.2% were stunted and 13.4% of children were wasted, of which 17.3% and 3.1% were severely stunted and wasted respectively. 46.3% of children were exclusively breastfed, in 28.4% breast-feeding continued till 2 years of age or more while only 5.4% of children were started on complimentary feeding at 6 months of age. The Dietary Diversity Score (DDS) was seen to be appropriate in 51.4% of children only. The above findings indicate that inappropriate feeding practices were associated with stunting (p=
Keywords: dietary diversity; feeding practices; malnutrition; nutritional status; stunting; wasting